Aplikasi Penjadwalan Daftar Jaga Perawat Dengan Menerapkan Algoritma Genetika : (Studi Kasus RSIA Muhammadiyah Probolinggo) - Ika Nur Habibah; Fawwaz Ali Akbar; Made Hanindia Prami Swari (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
A web-based nurse scheduling application utilizing a genetic algorithm is designed to optimize the arrangement of nurses’ work schedules in hospitals, which is often a challenge due to the need to consider various critical factors. The purpose of developing this application is to assist head nurses in efficiently creating nurse work schedules, while considering shift distribution, weekly working hour limits, provision of two days off per week, and the prohibition of assigning a night shift followed directly by a morning shift to ensure sufficient rest for nurses. This application is built using the CodeIgniter 3 framework, PHP programming language, and MySQL database. By leveraging the genetic algorithm, the system can automatically find the best schedule combinations and reduce violations of nurse scheduling rules. Test results show that the application can automatically generate schedules that comply with hospital regulations and requirements, and significantly accelerate the scheduling process compared to manual methods. Furthermore, the fitness value and schedule generation time produced are influenced by parameters such as population size, number of generations, mutation rate, and tournament size used.